2008
DOI: 10.1111/j.1360-0443.2008.02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy for human immunodeficiency virus/acquired immune deficiency syndrome among drug users: a systematic review

Abstract: While lower than other populations-especially among users of stimulants, incarcerated DU and patients with psychiatric comorbidities-adherence to HAART among HIV-positive DU can be achieved. Better adherence was identified among those engaged in comprehensive services providing HIV and addiction treatment with psychosocial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
169
4
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(187 citation statements)
references
References 65 publications
6
169
4
8
Order By: Relevance
“…In planning our recent systematic review (Malta et al 2008) and meta-analysis, we reviewed standard guidelines to conduct and report meta-analysis studies, which included the consolidated standards of reporting trials-CONSORT Moher et al 2001), the quality of reporting of meta-analyses-QUOROM (Moher et al 2000), the meta-analysis of observational studies in epidemiology (MOOSE) group , and the transparent reporting of evaluations with nonrandomized designs-TREND (Des Jarlais et al 2004). Since many of the selected studies were observational studies rather than clinical trials, the MOOSE recommendations were used to conduct and report the meta-analysis, while the TREND checklist (Version 1.0) was used as a guide for data abstraction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In planning our recent systematic review (Malta et al 2008) and meta-analysis, we reviewed standard guidelines to conduct and report meta-analysis studies, which included the consolidated standards of reporting trials-CONSORT Moher et al 2001), the quality of reporting of meta-analyses-QUOROM (Moher et al 2000), the meta-analysis of observational studies in epidemiology (MOOSE) group , and the transparent reporting of evaluations with nonrandomized designs-TREND (Des Jarlais et al 2004). Since many of the selected studies were observational studies rather than clinical trials, the MOOSE recommendations were used to conduct and report the meta-analysis, while the TREND checklist (Version 1.0) was used as a guide for data abstraction.…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies have found that HIVpositive drug users who have access to drug abuse and mental health treatment (Malta et al 2008), and particularly former drug users who are abstinent, can attain the same levels of adherence found among PLWHA who have never used illicit drugs (Crystal et al 2001) and can thus achieve similar survival rates compared to non-drug using populations (Wood et al 2008).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…El uso terapéutico de la misma, al menos en nuestro país, podría corresponderse con sujetos clínicamente más deteriorados o con un perfil socioeconómico más bajo (Ladero, Orejudo y Carrobles, 2005), lo que explicaría una peor adherencia y resultaría congruente con los resultados obtenidos. No obstante, estudios previos han planteado que la pertenencia a un programa terapéutico con metadona, frente a usuarios de drogas por vía parenteral sin seguimiento, podría suponer una mejora en la adherencia al tratamiento antirretroviral (Malta, Strathdee, Magnanini y Bastos, 2008), sobre todo en zonas marginales con elevada prevalencia de este tipo de consumo .…”
Section: Discussionunclassified
“…Yet, social support can address ART adherence concerns in drug-abusing and homeless populations. 34,35 And although the 2008 OARAC guidelines noted insufficient evidence regarding the timing of ART during TB treatment, recent studies demonstrate that ART during TB therapy reduces TB mortality among the most immunocompromised individuals in developing country settings. [36][37][38][39] As a result, OARAC released updated guidelines in 2012 formally recommending ART initiation within two weeks of TB treatment initiation for patients with 50 CD4 cells/mm 3 , 2-4 weeks after TB treatment initiation for those with severe clinical disease, and 8-12 weeks after TB treatment initiation for those without severe clinical disease.…”
Section: Discussionmentioning
confidence: 99%